2021
DOI: 10.1177/00111287211007728
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Victimization is Associated with a Significantly Greater Risk of Illicit Substance Use among US Female Adolescents: YRBS 2011 to 2017

Abstract: Bullying victimization among adolescents is associated with increased illicit substance use. This research estimates whether the association between bullying victimization and substance use is significantly greater among female adolescents. Using R software and the national Youth Risk Behavior Survey (2011, 2013, 2014, and 2017), interactions were estimated to determine the association between self-reported school or electronic bullying victimization and previous 30-day alcohol use, binge drinking, marijuana u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…This study suggests that experiencing bullying victimization is associated with substance use behaviors as early as middle school. Our findings add to previous research on this topic, which primarily finds associations for female youth, lacks diversity in the race/ethnicity categories examined, is limited to 1 setting, and/or focuses on outcomes in late adolescence and adulthood 6‐12 …”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This study suggests that experiencing bullying victimization is associated with substance use behaviors as early as middle school. Our findings add to previous research on this topic, which primarily finds associations for female youth, lacks diversity in the race/ethnicity categories examined, is limited to 1 setting, and/or focuses on outcomes in late adolescence and adulthood 6‐12 …”
Section: Discussionsupporting
confidence: 56%
“…In this study, the female and male groups demonstrated a nearly equal number of significant associations across measures of bullying victimization and substance use (Table 3), suggesting the importance of including both groups in prevention strategies. Although there were fewer associations for the Multiple Races, NH AIAN, and NH NHPI groups, the associations we report here add new evidence for these groups—as well as for the Asian group—which are largely not included in previous research 4‐12 . To help equitably prevent bullying victimization and substance use, cultural tailoring of messaging and interventions may be needed, accounting for cultural differences in perceptions, attitudes, and values about bullying and substance use.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…To date, little research has focused on the link between bullying and vaping. These studies generally find that adolescent bullying victimization is associated with vaping (Azagba et al, 2020; Boccio et al, 2022; Doxbeck, 2020; Hansen et al, 2021; Ihongbe et al, 2021; Pontes et al, 2021; Ragavan et al, 2021). For example, Azagba et al (2020) found that adolescents who were bullied daily or almost daily were likely to use e-cigarettes more frequently than adolescents who were not bullied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, we examine the associations between lifetime and last 30 day nicotine and marijuana vaping and bullying perpetration, bullying victimization, and bully-victim status for both in-person and cyberbullying. The majority of studies that have explored connections between vaping and bullying activities have measured vaping as whether or not an adolescent has used an e-cigarette (Azagba et al, 2020;Doxbeck, 2020;Hansen et al, 2021;Ihongbe et al, 2021;Pontes et al, 2021;Ragavan et al, 2021). While important to study, general measures of vaping treat all types of vaping similarly even though research has established that differential relationships exist between the various forms of vaping (Jackson et al, 2019(Jackson et al, , 2020.…”
Section: The Current Studymentioning
confidence: 99%